Spatial Distribution of Multipliers in Kalimantan Island Economy: An Inter-Regional Input-Output Analysis - Muchdie Muchdie (Signifikan: Jurnal Ilmu Ekonomi, 2017)
This paper provides the results of analysis on total multipliers and flow-on, sectoral-specific, and spatial-specific multipliers as important indicators for evaluating, planning and controlling regional development in Kalimantan Island economy. The model employed was Inter-Island Input-Output Model developed using new hybrid procedures with special attention on Island economy. The results show that firstly, the important sectors of Kalimantan Island economy could be based on total multipliers and flow-on effects of output, income and employment. Secondly, important economic sectors could be based on sector-specific multipliers effects; multipliers that occurred in own sector and other sectors. Thirdly, important economic sectors could be based on spatial-specific multipliers; multipliers that occurred both in own region and other regions. Finally, important economic sectors could be based on spatial distribution of flow-on; flow-on effects that occurred in own region as well as in other regions.DOI: 10.15408/sjie.v6i2.4736